Challenges in development and authorisation of gene therapy products - A. A. Soldatov; Zh. I. Avdeeva; D. V. Gorenkov; L. M. Khantimirova; S. G. Guseva; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2022)
There are a lot of diseases known today, which are caused by genetic abnormalities. Advances in genetics and biotechnology brought about gene editing technologies that can produce almost any gene, which ultimately led to the emergence of a new class of medicines - gene therapy products (GTPs). The aim of the study was to analyse international experience in development and authorisation of GTPs. The review highlights the challenges in GTP development, related to the search for an optimal approach to therapeutic gene delivery to the target cells. Viral vectors were shown to be a promising gene delivery system, with adenovirus (AV) and adeno-associated virus (AAV) based products demonstrating the highest efficacy and safety. The paper reviews current approaches to gene editing that allow modification of AVs and AAVs to improve GTP efficacy and safety. These modifications are carried out with the aim of, e.g., including a large therapeutic gene into a viral vector, decreasing viral protein expression levels, and decreasing viral vector immunogenicity. The review summarises GTP authorisation procedures in the USA and the European Union, including data on FDA and EMA subcommittees and departments entrusted with advisory functions. The paper mentions that there is one Russian-produced GTP authorised in the Russian Federation, and some other GTPs are in the pipeline. Therefore, the Russian regulatory framework and the Eurasian regulations and recommendations should be updated in order to accommodate for GTP development and authorisation.